Variasi Individual Peserta Didik - Elliya Nafilatul Afifah; Mokh Shoiful Fatoni (https://ejournal.insuriponorogo.ac.id/, 2024)
Education plays a pivotal role in national development, enabling individuals to enhance their potential and contribute positively to society. A critical aspect of educational success is acknowledging and managing the individual differences among learners. These differences, which include intelligence, learning styles, thinking patterns, temperament, and personality, significantly influence the learning process and outcomes. This study addresses the central question of how these individual differences can be effectively accommodated in educational settings to foster more inclusive and equitable learning environments. Utilizing a literature review methodology, the research examines various concepts, theories, and empirical findings from scholarly articles indexed in Google Scholar, Sinta, and Scopus, as well as relevant books. The data were analyzed using content analysis to identify key themes, patterns, and gaps in the current understanding of individual differences in learners. The findings suggest that a deep understanding of these differences is crucial for developing effective teaching strategies that meet the unique needs of each learner, thereby enhancing the overall quality of education and supporting personalized learning. This research provides a conceptual framework that can guide educators in creating responsive and adaptive educational practices that cater to the diverse needs of learners.